2015
DOI: 10.1021/ie504850n
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Stability in Silica Hydrogels

Abstract: Hydrogen peroxide (H 2 O 2 ) entrapment in silica hydrogels has potential to be used in various industrially important applications to increase H 2 O 2 stability. In this study, optimum conditions for hydrogel formation and H 2 O 2 stability were determined by varying the sodium content and initial H 2 O 2 concentration. Higher retention and better stability of H 2 O 2 were achieved with hydrogels at room temperature at low sodium concentration. Retention values of 89% were obtained with initial H 2 O 2 concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 37 publications
7
37
1
Order By: Relevance
“…One promising approach was introduced by Ż egliń ski and co-workersi n2 007, who described the prolonged antibacterial activity of silica xerogels entrapping 3.8 %H 2 O 2 ,w hich, stored at room temperature, retained 71 %o ft he entrapped peroxide after 63 days; [54] the same composite could be successfully used in place of 30 %H 2 O 2 in selective oxidation reactions. [57] More than 70 %o fH 2 O 2 was retained after 40 days of storage at room temperature ( Figure 9);t his shows that sol-gele ncapsulation in silica gels can be used to store high concentrations of H 2 O 2 in as table solid form. [57] More than 70 %o fH 2 O 2 was retained after 40 days of storage at room temperature ( Figure 9);t his shows that sol-gele ncapsulation in silica gels can be used to store high concentrations of H 2 O 2 in as table solid form.…”
Section: Emerging Usesmentioning
confidence: 96%
“…One promising approach was introduced by Ż egliń ski and co-workersi n2 007, who described the prolonged antibacterial activity of silica xerogels entrapping 3.8 %H 2 O 2 ,w hich, stored at room temperature, retained 71 %o ft he entrapped peroxide after 63 days; [54] the same composite could be successfully used in place of 30 %H 2 O 2 in selective oxidation reactions. [57] More than 70 %o fH 2 O 2 was retained after 40 days of storage at room temperature ( Figure 9);t his shows that sol-gele ncapsulation in silica gels can be used to store high concentrations of H 2 O 2 in as table solid form. [57] More than 70 %o fH 2 O 2 was retained after 40 days of storage at room temperature ( Figure 9);t his shows that sol-gele ncapsulation in silica gels can be used to store high concentrations of H 2 O 2 in as table solid form.…”
Section: Emerging Usesmentioning
confidence: 96%
“…Sudur et al . (), Sudur and Orbey () and Dogan et al . () observed that the amount and type of ions in the precursor during micro‐encapsulation has a major effect on the release rate from silica hydrogels.…”
Section: Introductionmentioning
confidence: 94%
“…Sudur et al . () evaluated the antimicrobial activity of H 2 O 2 ‐encapsulated hydrogels against Escherichia coli using the agar well diffusion method. Early experiments showed significant antimicrobial activity after 4 months of storage in a closed container at room temperature.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations